Feeding Outcomes for Infants with Bronchopulmonary Dysplasia Discharged on Nasogastric Feeds - Matharu, Preet; Cristea, A. Ioana; Slaven, James E.; Becker, Samantha; Niehaus, Jason Z. (American Journal of Perinatology, 2019)
Objective While previous studies regarding neonatal home feeding regimens have demonstrated a more favorable prognosis for nasogastric (NG) versus gastrostomy tubes (GT), institutional practices of discharge on NG feeds are varied, particularly for infants with bronchopulmonary dysplasia (BPD). Little is known regarding the risk factors for patients treated with GT postdischarge in premature infants with BPD. Our objective was to identify frequency and risk factors for treating premature infants with BPD discharged on NG feeds with GT.Study Design In this retrospective study, we included infants born at 30 weeks’ gestational age with BPD transitioning from a tertiary care center to home on NG feeds from 2010 to 2016.Results Of the 86 infants included in this study, 25 (29%) underwent GT placement at a median age of 264 days postdischarge. Fourteen (56%) were able to remove the GT at a median age of 979.5 days. Infants not requiring GT placement postdischarge were found to have a significantly higher ccipitofrontal circumference (p = 0.0089) and length (p = 0.0166) at discharge compared with infants with GT.Conclusion NG feeding for infants with BPD appears to be a viable treatment with fewer patients (29%) requiring GT placement. Gestational age and abnormal magnetic resonance imaging results were found to have a significant association with GT placement postdischarge.
Keywords: nutrition; bronchopulmonary dysplasia; gastrostomy tube; premature